Gully development and its spatio-temporal variability since the late 19th century in the northern Ethiopian Highlands - Frankl, Amaury (Afrika Focus, 2012)
This study validates previous research and indicates important land degradation by gullying in the second half of the 20th century in the Northern Ethiopian Highlands. In recent decades, local communities have however proven that with proper land management, this trend can be reversed. At a regional scale, gully networks are increasingly being stabilized and the landscape is greening. These developments have to be understood within a socio-economic environment of strong population growth and a low level of technological development, where most people rely on land resources for their livelihood, and where the fragility of the country’s economy is frequently being emphasized, for example when climatic shocks such as drought cause severe food shortages and famine. Socio-economical developments and their relation to land degradation should therefore be monitored closely. With an annual population growth rate of 2.37% (period 2000-2010, CSA, 2008) and a population size which is likely to double by 2050, the country faces immense challenges. Key is to rehabilitate land as a resource base for food security and ecosystem services, and to strengthen and diversify the rural economy in order to make local communities less dependent on land resources. Such challenges are embraced by many local, national and international programs, and should remain high on the agenda. As to other dryland environments, this study emphasizes that fast land degradation may occur when improper land management is applied. Most dramatic is the development of extensive and deep gully networks, which export large quantities of sediment through the ephemeral gully and river system and therefore jeopardize in situ agricultural production. Moreover, decreased agricultural production in the proximity of gullies can be expected as a result of the depressed water tables. With fast network expansion occurring, infrastructures may be damaged and costs related to future planning may be much higher than originally budgeted for. Downstream effects are also important. Water pollution caused by sediment and urban wastewater threatens human health and decreases agricultural production. As a result of a stronger ash ood regime, rivers – even those that are located many km downstream of the gullies – may respond strongly and geomorphic changes may cause infrastructures to be damaged (e.g., Billi, 2008).